Use of Presentation Applications as Learning Media - Pahmi Pahmi; Salman Jufri; Syamsul Fajri (Al-Hijr: Journal of Adulearn World, 2022)
The purpose of this study is to test whether the Canva application can or cannot be used as a medium for learning Arabic subjects for class VII MTsN 11 Subang Anak Batipuh specifically for mufradat. This study uses a qualitative research method with a descriptive approach. This research is motivated by the way students learn which plummets, showing that the understanding of students in lessons is very minimal, for that the existence of learning media makes school lessons easier to understand and understand for students and teachers who teach even easier with the existence of these learning media. The method used for media learning is using the Canva application. The problem that researchers face here is the lack of interest in students to memorize and practice, the researcher suggests with this application, student interest increases in studying Arabic mufradat because mufradat is a city of words in Arabic which has an important role to support us being able to speak Arabic. The conclusion of this research is that the design of learning media gets very good student responses to the Canva application, which is classified as active and student learning outcomes also increase. For children at MTsN Subang Anak, it is better to use the existing facilities more optimally and use them correctly, and developing them is well received by teachers and students.